2003
DOI: 10.1021/ja037390k
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation of Lineage-Committed Cells by a Small Molecule

Abstract: Combinatorial libraries were screened for molecules that induce mouse myogenic lineage committed cells to dedifferentiate in vitro. A 2,6-disubstituted purine, reversine, was discovered that induces lineage reversal of C2C12 cells to become multipotent progenitor cells which can redifferentiate into osteoblasts and adipocytes. This and other such molecules are likely to provide new insights into the molecular mechanisms that control cellular dedifferentiation and may ultimately be useful to in vivo stem cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
216
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(232 citation statements)
references
References 9 publications
11
216
1
4
Order By: Relevance
“…Two small purine molecules dubbed myoseverin and reversine that cause cellularization of C2C12 mouse myofibers have been screened from combinatorial chemical libraries (Chen, Zhang, Wu, Schultz, & Ding, 2004; Rosania et al., 2000). Myoseverin disrupted microtubules and upregulated genes for growth factors, immunomodulatory molecules, ECM remodeling proteases, and stress‐response genes, consistent with the activation of pathways involved in wound healing and regeneration, but did not activate the whole program of myogenic dedifferentiation in newt limbs (Duckmanton, Kumar, Chang, & Brockes, 2005).…”
Section: Formation Of the Accumulation Blastemamentioning
confidence: 99%
“…Two small purine molecules dubbed myoseverin and reversine that cause cellularization of C2C12 mouse myofibers have been screened from combinatorial chemical libraries (Chen, Zhang, Wu, Schultz, & Ding, 2004; Rosania et al., 2000). Myoseverin disrupted microtubules and upregulated genes for growth factors, immunomodulatory molecules, ECM remodeling proteases, and stress‐response genes, consistent with the activation of pathways involved in wound healing and regeneration, but did not activate the whole program of myogenic dedifferentiation in newt limbs (Duckmanton, Kumar, Chang, & Brockes, 2005).…”
Section: Formation Of the Accumulation Blastemamentioning
confidence: 99%
“…Dismantling of phenotypic structure and function is most visible in myofibers, but the molecular details of the process are largely uninvestigated for all limb cell types. A synthetic trisubstituted purine called myoseverin has been isolated from a combinatorial chemical library and found to cellularize C2C12 myotubes in vitro (Rosania et al, 2000;Chen et al, 2004). Myoseverin disrupts microtubules and upregulates genes for growth factors, immunomodulatory molecules, ECM remodeling proteases, and stress-response genes, consistent with the activation of pathways involved in wound healing and regeneration (Rosania et al, 2000), but does not activate the whole program of myogenic dedifferentiation (Duckmanton et al, 2005).…”
Section: Mechanisms Of Histolysis and Dedifferentiationmentioning
confidence: 99%
“…Recent studies suggest that dedifferentiation may be also possible in mammalian system (Odelberg et al, 2000;Tsai et al, 2002;Chen et al, 2004). Especially, the recent reports have shown that ectopic expression of msx1 in C2C12 myotubes can induce dedifferentiation of the myotubes to produce multipotent mononucleated cells (Odelberg et al, 2000), and a 2,6-disubstituted purine, reversine, can also induce dedifferentiation of C2C12 myoblasts to become mesenchymal progenitor cells (Chen et al, 2004). However, the C2C12 myogenic line may be heterogeneous because there is this novel evidence for a resident subset of cells with side population (SP) phenotype in the C2C12 line (Benchaouir et al, 2004), whereas SP cells themselves are growth-arrested and delayed in their ability to differentiate with behaving as multipotent stem cells (Zhou et al, 2001;Jankowski et al, 2002;Tamaki et al, 2003).…”
mentioning
confidence: 99%
“…These clone were further expanded in 25-cm 2 uncoated tissue-culture flasks to grow as spheres in suspension over the course of 8 wk (Figure 3Ac). We determined that cells in these clones could divide for more than 20 passages.One biochemical indicator of myoblast dedifferentiation would be the expression loss of Myf5 and MyoD, the markers of myogenic lineage-committed myoblasts (Odelberg et al, 2000;Parker et al, 2003;Chen et al, 2004). To investigate whether MBPCs are, in fact, the dedifferentiated myoblasts induced by CNTF, we investigated the expression levels of Myf5 and MyoD in the MBPCs.…”
mentioning
confidence: 99%